Application of smoothed continuous labile haemoglobin A1c reference intervals for identification of potentially spurious HbA1c results. Issue 8 (11th June 2014) - Loh, Tze Ping; Peng, Weng Kung; Chen, Lan; Sethi, Sunil Kumar
Abstract : Aims: We aim to develop smoothed continuous 2.5th and 97.5th percentile values for labile glycated haemoglobin A1c to glycated haemoglobin A1c (LHbA1c :HbA1c ) ratio against HbA1c, and apply them on our patient population for identification of potentially spurious HbA1c measurements. Methods: The LHbA1c and HbA1c were measured using Bio-rad Variant II high-performance liquid chromatography system. We recorded the LHbA1c and HbA1c values of 1555 patients who had normal chromatograms. Using these results, the 2.5th and 97.5th percentile reference limits of the LHbA1c :HbA1c ratio were described by LHbA1c :HbA1c =−0.0072×HbA1c +0.2925 and LHbA1c :HbA1c =−0.0132×HbA1c +0.5327, respectively. Results: When the reference intervals were applied on a separate 1000 patients, 34 and 29 of them had abnormally high and low LHbA1c :HbA1c ratios, respectively. Most of the observed high ratios were associated concurrently with elevated plasma glucose, anaemia, chronic liver and kidney diseases. A suppressed ratio was mostly associated with haemoglobin variants. Patients with heterozygous HbE or HbS variants tend to have lower LHbA1c :HbA1c ratios while the converse is true for heterozygous HbJ. Conclusions: The continuous LHbA1c :HbA1c ratio may be used to detect confounding factors or spurious HbA1c results, but its performance is confounded and reduced by the ambient plasma glucose.